Food Security and Sustainable Development: Overcoming Poverty through Sustainable Agriculture - Yusriadi, Yusriadi (Journal of Indonesian Scholars for Social Research, 2024)
This study examined the correlation between food security and sustainable development in the context of poverty alleviation through sustainable agriculture. Employing a qualitative approach, this study evaluated the effectiveness of sustainable agricultural practices in improving food security in poverty-prone areas. The data were collected from various sources, including interviews with farmers and secondary data analysis from government reports and international organizations. The study found that the adoption of sustainable agricultural practices such as organic farming systems, crop rotation, and the use of environmentally friendly technologies had a significant positive impact on agricultural productivity. This, in turn, leads to increased income for farmers and greater food availability, ultimately reducing poverty levels. Additionally, this study reveals that government policies and infrastructure support play a crucial role in facilitating the transition to sustainable agriculture. This study offers new insights into the significance of synergies between food security and sustainable development, and their contribution to poverty alleviation strategies. The results indicate the need for more comprehensive policies and a holistic approach when designing agricultural development programs. These programs should not only focus on production but also on social, economic, and environmental aspects.